Distinct molecular and immunological properties of circulating exosomes isolated from pediatric lung transplant recipients with bronchiolitis obliterans syndrome ‐ a retrospective study. (5th September 2020) - Sharma, Monal; Ravichandran, Ranjithkumar; Perincheri, Sudhir; Danziger‐Isakov, Lara; Heeger, Peter S.; Sweet, Stuart C.; Mohanakumar, Thalachallour
Abstract: Long‐term success following human lung transplantation is poor due to chronic rejection. We demonstrated circulating exosomes of lung origin during acute and chronic lung allograft rejection. We analyzed plasma from pediatric lung transplant recipients (LTxRs) enrolled in the CTOT‐C‐03 to determine whether circulating exosomes are released into circulation during bronchiolitis obliterans syndrome (BOS). Plasma exosomes were isolated, and human leukocyte antigens (HLA) were detected. Exosomes were analyzed for lung self‐antigens (SAgs), co‐stimulatory molecules transcription factors, major histocompatibility complex class II (MHC‐II), adhesion molecules, and 20S proteasome. Mice were immunized with exosomes from BOS or stable to determine their immunogenicity. Circulating exosomes from BOS LTxRs contained increased levels of SAgs, donor HLA class I, MHC‐II, transcription factors, co‐stimulatory molecules, and 20S proteasome compared with stable. Serial analysis of exosomes containing SAgs demonstrated that exosomes are detectable in the circulation before BOS. Mice immunized with exosomes from BOS, or stable, demonstrated that exosomes from BOS are distinct in inducing both humoral and cellular immune responses to SAgs. Circulating exosomes from BOS LTxRs elicit distinct humoral and cellular response. In addition, detection of SAgs on circulatory exosomes 12 months before diagnosis of BOS suggest that exosomes could serve as biomarker.